Comparative Study on Effect of Bacopa monniera, Omega Fatty Acids and Mesenchymal Stem Cells on Cold Stress Induced Neurodegeneration in Hippocampus of Wistar Rats - Saravana Kumar; Saraswathi P; Khin Thant Zin; Saied Reza Doustjalali; Danish Muzaffa; Jothi Priya; Gayathri Devi (Journal of Krishna Institute of Medical Sciences University, 2020)
Background: Natural and ayurvedic drugs are compared with stem cell therapy to suggest an improved treatment to enhance memory and combat stress in our day to day life. Aim and Objectives: The present study was aimed to compare the effect of traditional medicine Bacopa monniera (BM) with omega3 fatty acids and mesenchymal stem cells on cold stress induced neural changes in hippocampus of Wistar rats. Materials and Methods: Total 36 male rats divided into six groups. Group I was control in which rats were kept under ideal laboratory conditions, Group II was cold water swim stress in which rats were forced o to swim in the cold water maintained at 18±2 C for ten minutes for a period of one month, Group III was given stress followed by oral administration of normal saline as a control, Group IV was given stress for a month followed by oral administration of 80 mg/kg of BM extract, Group V in which cold water swim stress given for a month followed by oral administration of 60 mg/kg omega3 fatty acid treatment for a month, Group VI in which cold water swim stress given for a month followed by intravenous injection of mesenchymal stem cells treatment. The animals were studied on their behavioral changes, cortisol assay and histological analysis. Results: The results showed P<0.001, that is significant difference between the groups in their behavioral study, cortisol assay and total number of cells. Conclusion: All three drugs have significant effect in improving the memory, but when comparison was made, it was suggested that intravenous infusion of bone marrow derived mesenchymal stem cells was superior followed by BM and omega3 fatty acids.